Workshop of Classroom Action Research with The Elementary School Teachers - Kaswari Kaswari; Tahmid Sabri; Mastar Asran; Endang Uliyanti (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
The purpose of this community service activity is to provide training for elementary school teachers about classroom action research design techniques for elementary school teachers to do classroom action research in school or in their respective duties. Community service activities implemented are expected to provide benefits in the effort of teachers improve the quality of their understanding of classroom action research, so as to improve their skills in conducting research activities. By understanding and skills in conducting research, a teacher can improve and improve the quality of learning that ultimately impact on the achievement of competence development of learners in learning.